2019
DOI: 10.1038/s41598-019-54750-6
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami records of the last 8000 years in the Andaman Island, India, from mega and large earthquakes: Insights on recurrence interval

Abstract: As many as seven tsunamis from the past 8000 years are evidenced by sand sheets that rest on buried wetland soils at Badabalu, southern Andaman Island, along northern part of the fault rupture of the giant 2004 Aceh-Andaman earthquake. The uppermost of these deposits represents the 2004 tsunami. Underlying deposits likely correspond to historical tsunamis of 1881, 1762, and 1679 CE, and provide evidence for prehistoric tsunamis in 1300–1400 CE, in 2000–3000 and 3020–1780 BCE, and before 5600–5300 BCE. The sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…We agree with Somerville that the absence of sedimentary evidence for a tsunami near 900 CE in Aceh (Indonesia) and in the Andaman Islands (Rubin et al, 2017;Malik et al, 2019) does not preclude the likelihood of its occurrence, as more recent erosional events could have removed the deposit. For example, field studies in Sri Lanka (Moore et al, 2007) and Thailand (Szczuciński, 2012) described the limited preservation potential of the recent 2004 tsunami deposit due to the erosion generated by subsequent Monsoon rains.…”
supporting
confidence: 85%
“…We agree with Somerville that the absence of sedimentary evidence for a tsunami near 900 CE in Aceh (Indonesia) and in the Andaman Islands (Rubin et al, 2017;Malik et al, 2019) does not preclude the likelihood of its occurrence, as more recent erosional events could have removed the deposit. For example, field studies in Sri Lanka (Moore et al, 2007) and Thailand (Szczuciński, 2012) described the limited preservation potential of the recent 2004 tsunami deposit due to the erosion generated by subsequent Monsoon rains.…”
supporting
confidence: 85%
“…This would indicate perhaps that while these diseases are assumed to be relatively new to human experience as a whole, the evolutionary value of uniform behavioral response remains learned or passed down via myth, tales or other cultural means. A similar response to ancient, but recurrent catastrophic threat, was seen in the 2004 tsunami [169][170][171]. In fact, it seems that humans are devoid of any instinctual information concerning disease recognition.…”
Section: Cultural and Urban Factorsmentioning
confidence: 79%
“…In a recent study from South Andaman (Fig. 1), Malik et al (2019) have reported six paleo-tsunamis prior to the 2004 tsunami. Among these, younger tsunami depositions are linked to the historically reported earthquakes of 1881 (Mw 7.9; Car Nicobar), 1762 (Mw ≤8.5; Arakan Coast, Myanmar) and 1679 (magnitude unknown;north Andaman;Iyengar et al, 1999).…”
Section: Andaman and Nicobar Islandsmentioning
confidence: 99%